Oral contraceptives induced hepatotoxicity - Srikanth, B. Akshaya; Manisree, V. (International Journal of Basic & Clinical Pharmacology, 2017)
Oral Contraceptives are the pharmacological agents used to prevent pregnancy. These are divided as the combined and progestogen methods and are administered orally, transdermally, systemically and via vaginal route. All these methods contain both oestrogen and progestogen. Vigorous usage of oral contraceptives and anabolic steroids as associated with cholestasis, vascular lesions and hepatic neoplasm. Benign hepatic neoplasms are clearly associated with oral contraceptives. In this article we discuss the various hepatocellular complications like cholestasis, benign neoplasm and hepatocellular carcinoma occurred by oral contraceptives.